Edwardsiella tarda Bacteremia. A Rare but Fatal Water- and Foodborne Infection: Review of the Literature and Clinical Cases from a Single Centre. Issue 6 (2015) - Hirai, Yuji; Asahata-Tago, Sayaka; Ainoda, Yusuke; Fujita, Takahiro; Kikuchi, Ken
Abstract : BACKGROUND: Edwardsiella tarda bacteremia (ETB) can be a fatal disease in humans. OBJECTIVES: To determine the significant risk factors associated with death caused by ETB, and to examine the geographical, seasonal, environmental and dietary factors of the disease. METHODS: A retrospective, observational, case control study was performed. The PubMed MEDLINE and Japanese Medical Abstract Society (www.jamas.or.jp ) databases were searched for ETB case reports and meeting abstracts. In additon, retrospective chart reviews of patients with ETB at the Tokyo Women's Medical University Hospital (Tokyo, Japan) were conducted to evaluate the risk factors associated with death using multivariate analyses. RESULTS: The literature search yielded 46 publications, comprising 72 cases from the English (n=30), French (n=1), Spanish (n=1) and Japanese (n=14) literature. Five cases at the Tokyo Women's Medical University Hospital were also included. Of the included 77 cases, the mean age was 61 years and 39% of patients were female; 77.2% of the cases occurred between June and November, and 45.5% were reported in Japan. Dietary factors (raw fish/meat exposure) were reported for 10.4% of patients and 12.9% reported environmental (ie, brackish water) exposure. The overall mortality rate was 44.6%; however, this rate increased to 61.1% for ETB patients with soft tissue infections. Liver cirrhosis was determined to be an independent risk factor associated with death (OR 12.0 [95% CI 2.46 to 58.6]; P=0.00213) using multivariate analyses. DISCUSSION: To our knowledge, the present analysis was the first and largest multi-language review of ETB. Clinical characteristics of ETB resemble those of Aeromonas, typhoid fever and Vibrio vulnificus infections, in addition to sharing similar risk factors. CONCLUSION: ETB should be categorized as a severe food- and waterborne infection, which results in high mortality for patients with liver cirrhosis.